Evolutionary Fervor. - Grier, David Alan (Computer (00189162), 2008)
The article focuses on the evolution of computer software, programming and web browsers. The author explains how the metaphor of software evolution offers some insight into the nature of program development because it has provided computer scientists principles that suggest how large systems expand and develop. The author draws on the parallels between the concepts of software development and scientist Charles Darwin's theories of biological evolution. Attention is also given to the development of a new browser.